Separation and recovery technological process for copper element in composite copper foil
By using the prepared adsorbent in the composite copper foil for magnetic separation and recovery process, the efficient separation and recycling of copper elements in the composite copper foil is solved, and the recycling and environmental protection goals of resources are achieved.
Patent Information
- Application Number
- CN202510147988.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
How to efficiently and environmentally friendly separate and recover copper elements in composite copper foil, realize the recycling of resources, and reduce the impact on the environment.
A process flow is adopted, after ultrasonication of the composite copper foil in an acid mixture, the prepared adsorbent is added for stirring, and the solid powder containing copper elements is separated from the solution by magnetic separation technology. The adsorbent is prepared by a combination of crop straw biochar, iron oxide and oligomeric chitosan, which significantly improves the adsorption capacity of copper ions and is recovered through magnetic properties.
It realizes efficient separation and recycling of copper elements in composite copper foil, reduces treatment costs and environmental impact, and is in line with the concept of green and sustainable development.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite copper foil recycling and relates to a process flow for separating and recycling copper elements in composite copper foil. Background Art
[0002] In recent years, with the vigorous development of the new energy vehicle industry and the continuous advancement of energy storage technology, the demand for lithium batteries as core components has surged. At the same time, battery factories and vehicle manufacturers have put forward more stringent requirements for the high energy density, high safety, quality and efficiency improvement of lithium battery materials. In this context, composite current collectors, as an innovative material design, have shown great potential in improving battery energy density with their unique performance advantages, and have become a research hotspot in the industry. Among them, the new process composite copper foil is a typical representative. The composite copper foil is based on polymer materials, and metallic copper is precipitated on the upper and lower sides. Its structure is similar to a "sandwich", mainly composed of "copper-polymer-copper". Compared with traditional copper foil, the advantages of composite copper foil are good safety, improved energy density, and low mass production cost. However, with the rapid increase in the use of composite copper foil, how to efficiently and environmentally friendly separate and recycle the copper element in it to achieve resource recycling and reduce the impact on the environment has become a technical challenge that needs to be solved urgently. Summary of the invention
[0003] The purpose of the present invention is to provide a process flow for separating and recovering copper elements in composite copper foil, which has the characteristics of high separation efficiency.
[0004] The purpose of the present invention can be achieved by the following technical solutions: A separation and recovery process of copper elements in a composite copper foil, wherein the specific steps of the separation and recovery process are as follows: S1: Add the composite copper foil into the acid mixture, ultrasonicate at 50-70 °C for 1-2 h, take out the polymer film, and obtain a solution; S2: Add the adsorbent to the solution and stir at 45-55 °C and 650-750 r / min for 2-3 h to obtain a solid-liquid mixture; S3: Separating the copper-containing solid powder and solution in the solid-liquid mixture by magnetic separation; Wherein, the preparation method of the adsorbent is as follows: S2-1: The crop straw is calcined in a muffle furnace at a temperature of 400-500 °C for 1-2 h, then ball-milled in a ball mill for 1-2 h, and then irradiated with ultraviolet light for 8-10 h to obtain powder A; S2-2: 10 parts by weight of ferric chloride and 5 parts by weight of ferrous sulfate were mixed, added to 100 parts by weight of deionized water, ultrasonicated for 30 min, added with 10 parts by weight of powder A, adjusted the pH of the solution with sodium hydroxide solution, stirred at a speed of 550-750 r / min for 10-14 h, and then heated in an oven at 170-190 °C for 2-4 h, washed with deionized water and anhydrous ethanol, and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder B; S2-3: Powder B was added to deionized water so that the solid-liquid mass ratio was 1:10, and ultrasonic treatment was performed for 10 min. Then, oligochitosan was added, and ultrasonic treatment was performed for 10-20 min. The pH was adjusted to 4-6 with 6 M glacial acetic acid, and the mixture was stirred at 55 °C for 3-4 h. The mixture was washed with deionized water and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder C. S2-4: Add 5 parts by weight of powder C to 50 parts by weight of iminodisuccinic acid solution, add 50 parts by weight of PBS buffer, stir at 40-50°C at a speed of 500-600 r / min for 3-5 h, wash with deionized water and anhydrous ethanol, and then place in a vacuum drying oven at 60°C for 12 h to obtain the adsorbent.
[0005] As a preferred technical solution of the present invention, the polymer film in S1 is one of PP film, PET film and PI film.
[0006] As a preferred technical solution of the present invention, the acid mixture in S1 is a mixture of 1 M hydrochloric acid and 1 M nitric acid in a mass ratio of (1-3):1.
[0007] As a preferred technical solution of the present invention, the ultrasonic power in S1 is set to 7-9 kHz.
[0008] As a preferred technical solution of the present invention, the crop straw in S2-1 is one or more of corn straw, wheat straw, and rice straw.
[0009] As a preferred technical solution of the present invention, the ball milling speed in S2-1 is 200~300 r / min.
[0010] As a preferred technical solution of the present invention, the irradiation intensity in S2-1 is 500 μW / cm 2 , the ultraviolet wavelength is 200~280 nm.
[0011] As a preferred technical solution of the present invention, in S2-2, 2 M sodium hydroxide solution is used to adjust the solution pH to 9.5-10.5.
[0012] As a preferred technical solution of the present invention, the addition amount of the oligomolecular chitosan in S2-3 is 2-3 wt% of the total mass of the powder B and deionized water.
[0013] As a preferred technical solution of the present invention, the molar concentration of the iminodisuccinic acid solution in S2-4 is 0.2 M.
[0014] First, the crop straw is calcined at high temperature in a muffle furnace to remove volatiles and organic matter, forming a porous biochar. Subsequently, ball milling further refines the biochar particles, increases its specific surface area, and provides more adsorption sites. Ultraviolet irradiation treatment helps remove residual organic matter on the surface of biochar, while inducing changes in surface functional groups and enhancing its adsorption capacity for copper ions. Using crop straw-based biochar as the main adsorbent realizes the resource utilization of solid waste and saves recycling costs.
[0015] After the mixture of ferric chloride and ferrous sulfate is hydrolyzed to form iron oxides, these oxides form a load inside and on the surface of biochar. The iron oxides not only increase the chemical activity of the adsorbent, but also provide more effective adsorption sites. By adjusting the pH of the solution, the morphology and loading of iron oxides can be controlled. The subsequent heat treatment further consolidates the combination of iron oxides and biochar and improves the stability of the adsorbent. In addition, the introduction of iron oxides also gives biochar magnetic properties, which allows the adsorbent to be easily recovered through magnetic separation technology after adsorption is completed, greatly improving the treatment efficiency and recycling performance, and reducing the treatment cost and environmental impact.
[0016] The addition of oligomeric chitosan introduces abundant amino and hydroxyl functional groups into the adsorbent, which can form hydrogen bonds or coordination bonds with copper ions, thereby significantly improving the adsorption capacity of the adsorbent. The combination of oligomeric chitosan and biochar not only enhances the overall structural stability of the adsorbent, but also further improves the adsorption efficiency and selectivity through the synergistic effect of functional groups.
[0017] Iminodisuccinic acid is a green and environmentally friendly aminocarboxylic acid chelating agent with excellent chelating ability for copper ions. The coordinating atom N on the surface of the iminodisuccinic acid structure will coordinate with copper, fix the copper element in the ring structure and form a stable chelate; at the same time, the nitrogen atoms and oxygen atoms in its molecular structure may also serve as ion exchange sites to exchange with copper ions. The modification of iminodisuccinic acid may also improve the surface properties and pore structure of the adsorbent, so that the adsorbent's adsorption capacity for copper ions is further enhanced. In addition, iminodisuccinic acid has good degradation performance in nature, which is in line with the concept of green and sustainable development.
[0018] Beneficial effects of the present invention: The present invention significantly increases the adsorption sites and removes residual organic matter by calcining crop straw into porous biochar at high temperature, and then ball milling and ultraviolet irradiation treatment; further loading iron oxide on biochar not only improves the chemical activity, but also gives the biochar magnetic properties, which is convenient for magnetic separation and recovery, and reduces the processing cost. The addition of oligomeric chitosan introduces rich amino and hydroxyl functional groups, which form hydrogen bonds or coordination bonds with copper ions, significantly enhancing the adsorption capacity. In addition, it is modified with iminodisuccinic acid, and its coordination atom N forms a stable chelate with copper ions, while nitrogen and oxygen atoms serve as ion exchange sites, further improving the adsorption efficiency and selectivity. The adsorbent not only has strong adsorption capacity and high stability, but also has good degradation performance and recycling performance, which conforms to the green and sustainable development concept. DETAILED DESCRIPTION
[0019] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0020] In the embodiments of the present invention and the comparative examples: Ferric chloride: purchased from Shandong West Asia Chemical Co., Ltd.; Ferrous sulfate: purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd.; Sodium hydroxide: purchased from Jinan Feiyue Chemical Co., Ltd. Oligomeric chitosan: purchased from Jiangsu Duoyang Bioengineering Technology Co., Ltd.; Glacial acetic acid: purchased from Shanghai Denuo Chemical Co., Ltd.; Iminodisuccinic acid: purchased from Shanghai Yien Chemical Technology Co., Ltd.; Anhydrous ethanol: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; PBS buffer: purchased from Aibixin (Shanghai) Biotechnology Co., Ltd.
[0021] Embodiment 1: A separation and recovery process of copper elements in a composite copper foil, wherein the specific steps of the separation and recovery process are as follows: S1: Add the composite copper foil into the acid mixture, which is a mixture of 1 M hydrochloric acid and 1 M nitric acid in a mass ratio of 2:1, and ultrasonicate at 60 °C for 1.5 h with an ultrasonic power of 8 kHz. Take out the PP film to obtain a solution; S2: Add the adsorbent to the solution and stir at 700 r / min for 2.5 h at 50 °C to obtain a solid-liquid mixture; S3: Separating the copper-containing solid powder and solution in the solid-liquid mixture by magnetic separation; Wherein, the preparation method of the adsorbent is as follows: S2-1: The corn stalks were calcined in a muffle furnace at 450 °C for 1.5 h, then ball milled for 1.5 h at a speed of 250 r / min, and then irradiated with ultraviolet light for 9 h at an intensity of 500 μW / cm 2 , the ultraviolet wavelength is 256 nm, and powder A is obtained; S2-2: 10 parts by weight of ferric chloride and 5 parts by weight of ferrous sulfate were mixed, added to 100 parts by weight of deionized water, ultrasonicated for 30 min, added with 10 parts by weight of powder A, adjusted the solution pH to 10 with 2 M sodium hydroxide solution, stirred at 650 r / min for 12 h, then heated in an oven at 180 °C for 3 h, washed with deionized water and anhydrous ethanol, and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder B; S2-3: Powder B was added to deionized water so that the solid-liquid mass ratio was 1:10, and the mixture was ultrasonicated for 10 min. Then, 2.5 wt% of oligosaccharide by total mass of powder B and deionized water was added, and the mixture was ultrasonicated for 15 min. The pH was adjusted to 5 with 6 M glacial acetic acid, and the mixture was stirred at 55 °C for 3.5 h. The mixture was washed with deionized water and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder C. S2-4: Add 5 parts by weight of powder C to 50 parts by weight of 0.2 M iminodisuccinic acid solution, add 50 parts by weight of PBS buffer, stir at 45°C at a speed of 550 r / min for 4 h, wash with deionized water and anhydrous ethanol, and then place in a vacuum drying oven at 60°C for 12 h to obtain the adsorbent.
[0022] Embodiment 2: A separation and recovery process of copper elements in a composite copper foil, wherein the specific steps of the separation and recovery process are as follows: S1: Add the composite copper foil into the acid mixture, which is a mixture of 1 M hydrochloric acid and 1 M nitric acid in a mass ratio of 1:1, and ultrasonicate at 50 °C for 1 h with the ultrasonic power set to 7 kHz. Take out the PET film to obtain a solution; S2: Add the adsorbent to the solution and stir at 45 °C and 650 r / min for 2 h to obtain a solid-liquid mixture; S3: Separating the copper-containing solid powder and solution in the solid-liquid mixture by magnetic separation; Wherein, the preparation method of the adsorbent is as follows: S2-1: The wheat straw was calcined in a muffle furnace at 400 °C for 1 h, then ball milled for 1 h at a speed of 200 r / min, and then irradiated with UV light for 8 h at an intensity of 500 μW / cm 2 , the ultraviolet wavelength is 200 nm, and powder A is obtained; S2-2: 10 parts by weight of ferric chloride and 5 parts by weight of ferrous sulfate were mixed, added to 100 parts by weight of deionized water, ultrasonicated for 30 min, added with 10 parts by weight of powder A, adjusted the solution pH to 9.5 with 2 M sodium hydroxide solution, stirred at 550 r / min for 10 h, then placed in a 170 °C oven for 2 h, washed with deionized water and anhydrous ethanol, and dried in a 60 °C vacuum drying oven for 12 h to obtain powder B; S2-3: Powder B was added to deionized water so that the solid-liquid mass ratio was 1:10, and the mixture was ultrasonicated for 10 min. Then, 2 wt% of oligochitosan was added to the total mass of powder B and deionized water, and the mixture was ultrasonicated for 10 min. The pH was adjusted to 4 with 6 M glacial acetic acid, and the mixture was stirred at 55 °C for 3 h. The mixture was washed with deionized water and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder C. S2-4: Add 5 parts by weight of powder C to 50 parts by weight of 0.2 M iminodisuccinic acid solution, add 50 parts by weight of PBS buffer, stir at 40°C at a speed of 500 r / min for 3 h, wash with deionized water and anhydrous ethanol, and then place in a vacuum drying oven at 60°C for 12 h to obtain the adsorbent.
[0023] Embodiment 3: A separation and recovery process of copper elements in a composite copper foil, wherein the specific steps of the separation and recovery process are as follows: S1: Add the composite copper foil into the acid mixture, which is a mixture of 1 M hydrochloric acid and 1 M nitric acid in a mass ratio of 3:1, and ultrasonicate at 70 °C for 2 h with the ultrasonic power set to 9 kHz. Take out the PI film to obtain a solution; S2: Add the adsorbent to the solution and stir at 750 r / min for 3 h at 55 °C to obtain a solid-liquid mixture; S3: Separating the copper-containing solid powder and solution in the solid-liquid mixture by magnetic separation; Wherein, the preparation method of the adsorbent is as follows: S2-1: The rice straw was calcined in a muffle furnace at 500 °C for 2 h, then ball milled for 2 h at a speed of 300 r / min, and then irradiated with UV light for 10 h at an intensity of 500 μW / cm 2 , the ultraviolet wavelength is 280 nm, and powder A is obtained; S2-2: 10 parts by weight of ferric chloride and 5 parts by weight of ferrous sulfate were mixed, added to 100 parts by weight of deionized water, ultrasonicated for 30 min, added with 10 parts by weight of powder A, adjusted the solution pH to 10.5 with 2 M sodium hydroxide solution, stirred at 750 r / min for 14 h, then placed in a 190 °C oven for 4 h, washed with deionized water and anhydrous ethanol, and dried in a 60 °C vacuum drying oven for 12 h to obtain powder B; S2-3: Powder B was added to deionized water so that the solid-liquid mass ratio was 1:10, and the mixture was ultrasonicated for 10 min. Then, 3 wt% of oligosaccharide by weight of the total weight of powder B and deionized water was added, and the mixture was ultrasonicated for 20 min. The pH was adjusted to 6 with 6 M glacial acetic acid, and the mixture was stirred at 55 °C for 4 h. The mixture was washed with deionized water and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder C. S2-4: Add 5 parts by weight of powder C to 50 parts by weight of 0.2 M iminodisuccinic acid solution, add 50 parts by weight of PBS buffer, stir at 50°C at a speed of 600 r / min for 5 h, wash with deionized water and anhydrous ethanol, and then place in a vacuum drying oven at 60°C for 12 h to obtain the adsorbent.
[0024] Comparative Example 1: The preparation process of the adsorbent does not include step S2-2, and the remaining steps are the same as those in Example 1.
[0025] Comparative Example 2: The preparation process of the adsorbent does not include step S2-3, and the remaining steps are the same as those in Example 1.
[0026] Comparative Example 3: The preparation process of the adsorbent does not include step S2-4, and the remaining steps are the same as those in Example 1.
[0027] Comparative Example 4: The preparation process of the adsorbent does not involve the ultraviolet irradiation step, and the remaining steps are consistent with those in Example 1.
[0028] The content of copper in the solution of step S3 of the embodiment and the comparative example was determined by ICP-MS, and the experimental data are summarized in the following table.
[0029]
[0030] It can be seen from the data of the embodiments and comparative examples that the polymer film and the copper element in the composite copper foil can be efficiently separated by the process flow of the present invention.
[0031] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A process for separating and recovering copper elements in composite copper foil, characterized in that: The specific steps of the separation and recovery process are as follows: S1: Add the composite copper foil into the acid mixture, ultrasonicate at 50-70 °C for 1-2 h, take out the polymer film, and obtain a solution; S2: Add the adsorbent to the solution and stir at 45-55 °C and 650-750 r / min for 2-3 h to obtain a solid-liquid mixture; S3: Separating the copper-containing solid powder and solution in the solid-liquid mixture by magnetic separation; Wherein, the preparation method of the adsorbent is as follows: S2-1: The crop straw is calcined in a muffle furnace at a temperature of 400-500 °C for 1-2 h, then ball-milled in a ball mill for 1-2 h, and then irradiated with ultraviolet light for 8-10 h to obtain powder A; S2-2: 10 parts by weight of ferric chloride and 5 parts by weight of ferrous sulfate were mixed, added to 100 parts by weight of deionized water, ultrasonicated for 30 minutes, added with 10 parts by weight of powder A, adjusted the pH value of the solution with sodium hydroxide solution, stirred at a speed of 550-750 r / min for 10-14 hours, and then placed in a 170-190 ℃ oven for 2-4 hours, washed with deionized water and anhydrous ethanol, and dried in a 60 ℃ vacuum drying oven for 12 hours to obtain powder B; S2-3: Powder B was added to deionized water so that the solid-liquid mass ratio was 1:10, and ultrasonic treatment was performed for 10 min. Then, oligochitosan was added, and ultrasonic treatment was performed for 10-20 min. The pH was adjusted to 4-6 with 6 M glacial acetic acid, and the mixture was stirred at 55 °C for 3-4 h. The mixture was washed with deionized water and dried in a vacuum drying oven at 60 °C for 12 h to obtain powder C. S2-4: Add 5 parts by weight of powder C to 50 parts by weight of iminodisuccinic acid solution, add 50 parts by weight of PBS buffer, stir at 40-50°C at a speed of 500-600 r / min for 3-5 h, wash with deionized water and anhydrous ethanol, and then place in a vacuum drying oven at 60°C for 12 h to obtain the adsorbent.
2. The process for separating and recovering copper from composite copper foil according to claim 1, characterized in that: The polymer film in S1 is one of PP film, PET film and PI film.
3. The process for separating and recovering copper from composite copper foil according to claim 1, characterized in that: The acid mixture in S1 is a mixture of 1 M hydrochloric acid and 1 M nitric acid in a mass ratio of (1-3):
1.
4. The process for separating and recovering copper from composite copper foil according to claim 1, characterized in that: The ultrasonic power in S1 is set to 7-9 kHz.
5. The process for separating and recovering copper from composite copper foil according to claim 1, characterized in that: The crop straw in S2-1 is one or more of corn straw, wheat straw, and rice straw.
6. The process for separating and recovering copper from composite copper foil according to claim 1, characterized in that: The ball milling speed in S2-1 is 200-300 r / min.
7. The process for separating and recovering copper from composite copper foil according to claim 1, characterized in that: The irradiation intensity in S2-1 is 500 μW / cm 2 , the ultraviolet wavelength is 200~280 nm.
8. The process for separating and recovering copper from composite copper foil according to claim 1, characterized in that: In the S2-2, 2 M sodium hydroxide solution is used to adjust the solution pH to 9.5-10.
5.
9. The process for separating and recovering copper from composite copper foil according to claim 1, characterized in that: The amount of oligochitosan added in S2-3 is 2-3 wt% of the total mass of powder B and deionized water.
10. The process for separating and recovering copper from composite copper foil according to claim 1, characterized in that: The molar concentration of the iminodisuccinic acid solution in S2-4 is 0.2 M.
Citation Information
Patent Citations
Method for recycling copper from waste circuit board
CN101270411A
Composite Copper Foil And Manufacturing Method Therefor
CN103963376A
Method for recovering copper from used circuit board
CN106676577A
Recycling process for copper in copper foil waste water
CN107815546A
Preparation method of ultrathin composite copper foil and ultrathin composite copper foil
CN117265470A